Antimicrobial Use and Management of Childhood Diarrhea at Community Drug Retail Outlets in Eastern Ethiopia: A Matched Questionnaire-Based and Simulated Patient-Case Study - Edessa D; Sisay M; Hagos B; Amare F (Dove Medical Press, 2022)
Dumessa Edessa,1 Mekonnen Sisay,2 Bisrat Hagos,3 Firehiwot Amare4 1Department of Clinical Pharmacy, School of Pharmacy, College of Health and Medical Sciences, Haramaya University, Harar, Ethiopia; 2Department of Pharmacology and Toxicology, School of Pharmacy, College of Health and Medical Sciences, Haramaya University, Harar, Ethiopia; 3Department of Social Pharmacy, School of Pharmacy, College of Health and Medical Sciences, Haramaya University, Harar, Ethiopia; 4Department of Pharmacology and Clinical Pharmacy, School of Pharmacy, College of Health Sciences, Addis Ababa University, Addis Ababa, EthiopiaCorrespondence: Mekonnen Sisay, Department of Pharmacology and Toxicology, School of Pharmacy, College of Health and Medical Sciences, Haramaya University, P.O. Box, 235, Harar, Ethiopia, Email mekonnensisay27@yahoo.comIntroduction: Antimicrobial agents have saved millions of lives worldwide. However, inappropriate use has become a global concern leading to the emergence and spread of antimicrobial resistance (AMR). In this regard, the dispensing practices of pharmacy professionals in the community drug retail outlets (CDROs) plays a central role. Therefore, this study was aimed to assess the knowledge and dispensing practices of pharmacy professionals in the management of childhood diarrhea in CDROs of Eastern Ethiopia.Methods: A community based cross-sectional study was conducted in 100 randomly selected CDROs in Eastern Ethiopia from 1 August to 30 September 2020. Data were collected with a structured questionnaire matched with a simulated patient case. Descriptive statistics were employed to summarize variables. Cohen's Kappa was analyzed to measure the degree of agreement between questionnaire-based and simulated patient-based methods. Binary logistic regression analysis was conducted to determine factors associated with inappropriate dispensing practice.Results: Majority of the participants were aged 25- 34 years (median: 29 years). High proportion of them were male (65%) and had work experiences of two or more years. Majority (61%) of the professionals were knowledgeable about AMR. Out of 2886 scores, 745 scores were agreed on Cohen's Kappa interrater agreement scale with the overall percent agreement between the two methods being 26.0%. Besides, about 67% of dispensing practices to the simulated patient case was found inappropriate. On the multivariate analysis, insufficient knowledge of retailers on AMR was significantly associated with the inappropriate dispensing of antimicrobial agents.Conclusion: A considerable proportion of retailers had insufficient knowledge regarding the emergence and spread of AMR. Only a quarter of their questionnaire-based knowledge response agreed with simulated-patient-based actual practice, indicating weak agreement between the two methods and high level of inappropriate practice. Besides, insufficient knowledge of retailers was significantly associated with their inappropriate dispensing of antimicrobials.Keywords: diarrhea, pediatrics, antimicrobial use, CDROs, Ethiopia